Women street artists of Latin America : art without fear = Grafiteras y muralistas en América Latina : arte sin miedo - Cassandra, Rachel (Manic D Press, 2015)
In this groundbreaking, in-depth look at a rarely explored perspective of street art, more than twenty female artists from seven nations in Latin America discuss themes of social justice, artist process, community, visibility, feminism, and more. A bilingual edition packed with full-color photographs and interviews, this revealing exploration of contemporary street art includes work from Colombia, Peru, Panama, El Salvador, Nicaragua, Guatemala, and Mexico. Viva!